A developmental synapomorphy of squamate reptiles. Issue 6 (23rd September 2019) - Stewart, James R.; Blackburn, Daniel G.
Abstract: The reptilian clade Squamata is defined primarily by osteological synapomorphies, few of which are entirely unambiguous. Studies of developing squamate eggs have revealed a uniquely specialized feature not known to occur in any other amniotes. This feature—the yolk cleft/isolated yolk mass complex—lines the ventral hemisphere of the egg. During its formation, extraembryonic mesoderm penetrates the yolk and an exocoelom (the yolk cleft [YC]) forms in association with it, cutting off a thin segment of yolk (the "isolated yolk mass" [IYM]) from the main body of the yolk. The YC–IYM complex has been observed and described in more than 65 squamate species in 12 families. In viviparous species, it contributes to the "omphaloplacenta, " a type of yolk sac placenta unique to squamates. The only squamates known to lack the IYM are a few highly placentotrophic skinks with minuscule eggs, viviparous species in which it clearly has been lost. Given its absence in mammals, chelonians, crocodylians, and birds, the YC–IYM complex warrants recognition as a developmental synapomorphy of the squamate clade. As in extant viviparous lizards and snakes, the YC–IYM complex presumably contributed to the placenta of extinct viviparous squamates. Abstract : A unique pattern of development of the fetal membranes of lizards and snakes generates a shared, derived structure of the yolk sac, the yolk cleft–isolated yolk mass complex, that characterizes this lineage of amniotes.